Effect of cinnamon (Cinnamomum zeylanicum) bark oil on heat stress-induced changes in sperm production, testicular lipid peroxidation, testicular apoptosis, and androgenic receptor density in developing Japanese quails - Türk, G; Şimşek, Üg; Çeribaşı, Ao; Çeribaşı, S; Özer Kaya, Ş; Güvenç, M; Çiftçi, M; Sönmez, M; Yüce, A; Bayrakdar, A; Yaman, M; Tonbak, F (My University, 2015)
The aim of this study was to investigate the effect of cinnamon bark oil (CBO) on heat stress (HS)-induced changes in sperm production, testicular lipid peroxidation, testicular apoptosis, and androgenic receptor (AR) density in developing Japanese quails. Fifteen-day-old 90 male chicks were assigned to two main groups. The first group (45 chicks) was kept in a thermoneutral room at 22 C for 24 h/day. The second group (45 chicks) was kept in a roomwith high ambient temperature at 34 C for 8 h/day (from9AM–5 PM) and at 22 C for 16 h/day. Each of these two main groups was then divided into three subgroups (CBO groups 0, 250, 500 ppm) consisting of 15 chicks (six treatment groups in 2 3 factorial order). Each of subgroups was replicated for three times and each replicate included five chicks. Heat stress caused significant decreases in body weight, spermatid and testicular sperm numbers, the density of testicular Bcl-2 (antiapoptotic marker) and AR immunopositivity, and significant increases in testicular lipid peroxidation level, the density of testicular Bax (apoptoticmarker) immunopositivity, and a Bax/Bcl-2 ratio along with some histopathologic damages. However, 250 and 500 ppm CBO supplementation provided significant improvements inHS-induced increased level of testicular lipid peroxidation, decreased number of spermatid and testicular sperm, decreased densities of Bcl-2 and AR immunopositivity, and some deteriorated testicular histopathologic lesions. In addition, although HS did not significantly affect the testicular glutathione level, addition of both 250 and 500 ppm CBO to diet of quails reared in both HS and thermoneutral conditions caused a significant increase when compared with quails without any consumption of CBO. In conclusion, HS-induced lipid peroxidation causes testicular damage in developing male Japanese quails and, consumption of CBO, which has antiperoxidative effect, protects their testes against HS.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Cinnamon Heat stress Lipid peroxidation Androgenic receptor Apoptosis Quail